Identidad personal - Bocanegra Rodrguez, Andrea Victoria (2019)
The session entitled We identify our personal characteristic which strengthen our personal identity and we value ourselves as unique and unrepeatable human beings. Was carried out according to the Curricular Area of Personal Development, Citizenship and Civics of a third grade class of the secondary school I.E. Pedro Mercedes Urea._x000D_ The aim of the session is that the student identify their personal characteristics which strengthen their personal identity and value themselves as unique and unrepeatable human beings